Water Supply System in the Town atop of the Plateau of Eski-Kermen - Elzara Aiderovna Khairedinova (Античная древность и средние века)
Archaeological researches at the plateau of Eski-Kermen and in its environs discovered the sites of the structures which provided water supply to the town. In order to deliver drinking water to the inhabitants of the castle, in the late-sixth century they carved stairs into the rock at the very edge of the eastern precipice of the plateau, down to a natural source of water, and built ceramic pipe for water flowing under gravity from natural springs in the upper reaches of the Bilderan ravine to the south-eastern foot of the plateau, where it was collected in a specially built water cistern. Thence the townspeople took water to the top of the plateau manually or with baggage-cattle, going by stairs intentionally carved in rock and leading to the eastern sally port. As for the household needs, the townsfolk used rainwater collected by a network of drain gutters and cisterns carved in rock of their households. Obviously, the Byzantine engineers who built the castle on the plateau provided it with water taking into account the rules commonly accepted in their period and described by Flavius Vegetius Renatus’ treatise on warfare ca 400 AD, which was also popular in the Middle Ages.